Structural plasticity and network dynamics in the dorsal hippocampus - accumbal circuitry - Koren, V (2018)
The dorsal hippocampus has been implicated in the encoding of contextual information with particular involvement in spatial navigation. The nucleus accumbens is thought to promote the translation of higher order cognitive modalities into motor function directives. The dorsal hippocampus-accumbal circuitry has been postulated to promote the acquisition, consolidation and reinstatement of context specific reward seeking behaviour. However, the corresponding anatomical connectivity and physiological underpinnings of the translation of spatial representations into behavioural directives have not yet been established. This thesis entails the first study of the hippocampal dCA1-accumbal pathway whereby two complementary approaches were employed. Synaptic plasticity mechanisms, believed to underly experience dependent functional adaptations in the hippocampus and nucleus accumbens, have been shown to correlate with structural changes in dendritic spine morphology. For the sake of their study, invasive techniques have been established, however have been shown to incur significant damage to associated circuitries, rendering insights into structural plasticity in deep brain regions challenging. This thesis entails the first full in vitro and in vivo proof of principle of a new approach toward minimally invasive high resolution deep brain imaging of dendritic spines utilising adaptive optics and holographic light propagation through a single optical fibre, thinner than a human hair. This technology reduces the footprint and thus resulting tissue damage by two orders of magnitude while maintaining diffraction limited resolution. This work might facilitate future investigations of structural synaptic plasticity in deep brain circuitries such as the hippocampal dCA1-accumbal pathway (supervisor: Prof. Dr. Nigel Emptage). There has been indication that spatial information guided behaviour might be dependent on a functionally intact integrated dorsal hippocampus - accumbal circuitry. In order to study the downstream effect of dorsal hippocampal spatial information processing on the network dynamics of the accumbal circuitry, large scale multichannel electrophysiological recordings combined with optogenetic stimulation were employed simultaneously in both structures. dCA1 pyramidal cell long range projections were shown to mono-synaptically drive the activity of parvalbumin expressing interneurones in the NAc which in turn orchestrate the activity of medium spiny neurons through feed forward inhibition in a context dependent manner. This facilitates the selective activity of discrete medium spiny neuron cohorts and supports the translation of neural representations of space into spatial appetitive behaviour. Furthermore, this work might help to conceptualise how the nucleus accumbens can act as a gateway for converging and potentially competing input from different corticolimbic systems (supervisor: Ass. Prof. Dr. David Dupret).